Learning contracts in clinical education. - Renner JJ; Stritter FT; Wong HD (Radiologic Technology)
This study explored the outcomes of using learning contracts in a radiologic science program. Telephone surveys of contract learning participants and other radiologic science graduates provided data regarding graduate career satisfaction, lifelong learning habits and attitudes toward learning. Statistical comparison data found that contract learning participants reported higher job satisfaction, participated more in continuing education, demonstrated more self-motivation and independence, felt less competitive and anxious about courses and grades and felt more involved in their clinical courses.